A light burden: cultural discourse of light in Japan. Issue 1 (7th July 2020) - Hui, Lok Hang
Abstract : Purpose: This paper explores the sensory experiences and cultural meanings of light in Japan in relation to Japanese changing lighting practices. It demonstrates that these sensory experiences and cultural meanings form an integral part of social life in Japan. Design/methodology/approach: This paper adopts a blended approach that combines historical research and ethnographic data in the research on the meanings of light. The findings are presented in three parts. Two of them describe the social history of light, and the third draws on ethnographic data collected in suburban Japan. Findings: The findings suggest that light in Japan has maintained a close symbolic connection with certain positive values despite the changing lighting practices. For example, light is related to cleanliness in early historical records on candle-making. In post-war Japan, new light metaphors such as "bright family" were invented to accommodate new aspirations for modernity and progress. In the latest development, the moral dimension of light is emphasised. This is evident in the concerns on being seen as a "bright person", a person with a cheerful personality. Light in this way is related to the sensory experience of feeling a "social weight", the pressure for one to act according to social norms. Originality/value: This paper contributes to our anthropological understandings of light. It also provides a local case study of Japan, supported by original ethnographic research conducted by the author.